Direct evaluation of chemical potentials in substitutional solid solutions from monte carlo simulations - 임상호; G. E. Murch; W. A. Oates (TAYLOR & FRANCIS, 1990)
A new method for the rapid, direct evaluation of the component chemical potentials in substitutional solid solutions from a single Monte Carlo simulation is described. The method is carried out by using the removal or addition of a test-site. The reliability of the test-site method is evaluated for binary solutions on a square lattice with first and second nearest-neighbour interactions and on the b.c.c. lattice with nearest-neighbour interactions. The results obtained are compared with those from the exact solution (for the equi-atomic composition on the square lattice) and with those obtainable from Monte Carlo simulations by less direct routes. Both above and below the critical temperature the new method is found to be highly satisfactory. The new method has a distinct advantage over previous methods in being equally applicable to the calculation of component chemical potentials in multi-component solutions. ？ 1990 Taylor & Francis Ltd.